Bentuk dan Fungsi Onomatope dalam Webtoon Diary Mystery Karya Febs - Lia, Ema Aprel; Shalima, Irsyadi; Diani, Winasti Rahma (Kajian Bahasa dan Sastra (KABASTRA), 2024)
This research is motivated by the phenomenon of onomatopoeia in the Webtoon comic Diary Mystery Karya Febs. In addition to speech balloons and narrative text, comics often feature sound imitation effects called onomatopoeia. Onomatopoeia in comics has its own form and function. The habit of readers who are too focused on illustrations and speech balloons when reading comics, makes the existence of onomatopoeia ignored and seems to have no function. This causes onomatopoeia to be less recognized by readers. Therefore, the purpose of this study is to describe the form and function of onomatopoeia in Webtoon Diary Mystery by Febs. The reason for choosing Webtoon-based comics as a research source is because digital comics are currently in great demand by readers. In addition, comics with this horror genre were chosen because they contain various onomatopoeias. The theoretical foundation of this research is the theory of onomatopoeia form by Thomas & Clara (2004) and the theory of onomatopoeia function by Brown. This research uses a descriptive qualitative research design with data collection techniques using the methods of listening, note taking, and documentation, and the data analysis uses the referential pairing method.